At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
@whpalmer4 can u help me?
Does anybody know this?
you want to multiply one of the equations by some constant value, so that when you add them together, one variable will add to zero
Multiply by -2?
notice if you multiply the second by (-2), you get 4x + y = 4 -4x -14 y = -56 -----------------
then when you add the two equations, the x term will drop out (-4 + 4) = 0x
you see that
Yes I do so the right answer is D?
no, that example i just did multiplied the second by -2
Okay but how do I find the answer?
so, instead, how would you make the Y term drop out
Multiply by -1?
try -7 times the first equation (-7)(4x + y = 4 ) 2x + 7y = 28
gives -28x - 7y = -28 2x + 7y = 28 ------------------
adding equation 1 to equation 2 now, the y term goes to zero -26x + 0y = 0
so -26x = 0 x=0 plug into either to get the y
x=0 , y=4 to solve systems of linear eqn you can - muyltiply equations by constants add equations together switch order of equations
I ended up with 43=28 when plugged into the 2nd equation I don't know If I done it wrong.
I dont know what I am doing that I dont get the answer
start system 4x + y = 4 2x + 7y = 28 --------------- multiply first equation through by -7 to get -28x - 7 y = -28 2x + 7y = 28 -------------------
So I plug -7 to each of those equations the positive and the negative one?
adding the equations together eliminates y, what the instructions say to do -28x + 2x - 7y + 7y = -28 + 28 -26x =0
no, multiply each term in the first equation by a -7
Okay so the answer is 3?
multiply first equation through by -7 to get , second equation is not changed -28x - 7 y = -28 2x + 7y = 28 -------------------
Yes so the 3rd choice
th epoint of that was to eliminate the y variable when you add the two equations together
-26x = 0
and if you want to find y, plug x=0 into either of the equations
4x + y = 4 2x + 7y = 28
y = 4, should be the same in both , or you messed up
Yes I got that so 4=4
x = 0, so 4(0) + y = 4 ----->y = 4 2(0) + 7y = 28 -----7y = 28 ---->y = 4 same y=4 from both equations when x=0
Okay I dont get whats the answer should be
another answer they dont include, was what i did at the very start, i figured y first, multiplied second equation by -2, so when added the x term goes away
So which option should I pick then?
The third one, we multiplied the fisrt by -7 to get that Which of the following actions creates an equivalent system such that, when combined with the other equation, one of the variables is eliminated? -when combined means when you add them together, one variable will go to zero, like the -7y + 7y = 0y , y is eliminated
Okay can you help me with one more question?
just takes a few practice probs to get it down,
sure i can do one more
Determine the solution to f(x) = g(x) using the following system of equations f(x) = 5.5x − 13 g(x) = −5x + 18.5 x = 1 x = 2 x = 3 x = 4
I remember doing this but cant remember how
both f(x) and g(x) are functions on the XY plane. when f(x) = g(x), the two functions intersect at the same point (x,y)
Can u show me how to solve it?
set them equal f(x) = g(x) 5.5x - 13 = -5x + 18.5
add 5x to both sides
like this 5.5x - 13 - -5x +18.5 5x 5x
10.5x - 13 = 18.5 add 13 both sides 10.5x = 31.5
divide both sides by 10.5 1x = 31.5 / 10.5
Okay then divide by 10.5
x = 3
yep, the goal is to isolate x by itself
Okay thank you very much for the help!
no prob, anytime